Mitigation of Air Pollutants by UV-A Photocatalysis in Livestock and Poultry Farming: A Mini-Review - Lee, Myeongseong; Koziel, Jacek A.; Li, Peiyang; Jenks, William S. (Catalysts, 2022)
Ultraviolet (UV)-based photocatalysis has been the subject of numerous investigations focused on mitigating undesirable pollutants in the gas phase. Few works report on applications beyond the proof of the concept. Even less is known about the current state of the art of UV photocatalysis in the context of animal agriculture. A growing body of research published over the last 15 years has advanced the knowledge and feasibility of UV-A photocatalysis for swine and poultry farm applications. This review paper summarizes UV-A photocatalysis technology’s effectiveness in mitigating targeted air pollutants in livestock and poultry farms. Specifically, air pollutants include odor, odorous VOCs, NH3, H2S and greenhouse gases (CO2, CH4, N2O). We trace the progression of UV-A photocatalysis applications in animal farming since the mid-2000 and developments from laboratory to farm-scale trials. In addition, this review paper discusses the practical limitations and outlines the research needs for increasing the technology readiness and practical UV application in animal farming.